2009
DOI: 10.1111/j.1463-1318.2008.01693.x
|View full text |Cite
|
Sign up to set email alerts
|

Mortality risk analysis following routine vs selective defunctioning stoma formation after total mesorectal excision for rectal cancer

Abstract: The results of this review support the routine construction of a protective stoma. However, selective use of a DS is justified from a patient safety point of view if the CAL-rate and its related mortality are limited. Each unit should audit its performance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
20
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 60 publications
0
20
0
1
Order By: Relevance
“…Some authors have reported a lower incidence of anastomotic leakage and reduced morbidity in patients with defunctioning stomas and have recommended the routine use of it [20,21]. Other authors have experienced a similar rate of anastomotic dehiscence in patients with or without temporary stomas, with the unique advantage of reduced disastrous clinical consequences in ostomatous patients [6,22].…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Some authors have reported a lower incidence of anastomotic leakage and reduced morbidity in patients with defunctioning stomas and have recommended the routine use of it [20,21]. Other authors have experienced a similar rate of anastomotic dehiscence in patients with or without temporary stomas, with the unique advantage of reduced disastrous clinical consequences in ostomatous patients [6,22].…”
Section: Discussionmentioning
confidence: 94%
“…Some authors have recommended routine use of a temporary stoma to reduce the rate of and morbidity from anastomotic leakage [20,21]. In contrast, other authors have discouraged the routine use of temporary stomas, preferring selective use.…”
mentioning
confidence: 99%
“…Pata et al analysed four clinical randomized studies and found more anastomotic leakages (24% vs. 9.6%) as well as reinterventions (88.6% vs. 11.8%) and a higher mortality in the group without stoma (4.5% vs. 0%) [48]. Therefore, the choice of a selective approach has to be carefully considered and even experienced surgeons sometimes find it difficult to predict which patient will have an anastomotic leak when risk factors are absent [5].…”
Section: Discussionmentioning
confidence: 96%
“…Temporary stomas have been shown to be protective [1][2][3][4] , and temporary diversion adds little to the overall morbidity of an operation. 21 However, proximal diversion is not benign.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3][4] As technology and surgical techniques are improving, a greater number of patients are undergoing sphincter sparing surgery, 5 many with temporary diversion. Given the low morbidity and potential advantages of diversion, it has been suggested that most rectal cancer patients should have a diverting stoma.…”
Section: Introductionmentioning
confidence: 99%